Model Pemikiran Islam dalam Konteks Pengembangan Pendidikan; (Studi Terhadap Madzhab-Madzhab Pendidikan Islam) - Khotibul Umam (FALASIFA : Jurnal Studi Keislaman, 2016)
Education is seen as one of the aspects that have a fundamental role in shaping the Islamic generation of superior quality. Thus, education is expected to producequality human and responsible and able to anticipate problems and challenges inthe future. Education in the broader meaning senantiasi stimulate and accompanythe changes and development of mankind, while the educational efforts areexpected to deliver and guide the changes and the development of life and humanlife. Islamic education is one field of Islamic studies who received attention fromscientists. This, in addition to a very strategic role in order to improve the humanresources (HR) also inside Islam there are many different education very complexproblem. To answer the challenges and changes of the times and the era ofmodernity, both in the context of religion, science and technology (IPTEK),social, cultural, economic, human rights, the environment, and the issue ofcultural in general, can be observed through the four modes of thought all Islamic,ie textual salafi, traditional mazhabi, modernist and neo-modernist. Meanwhile, inan effort to develop the Islamic education there are four streams are progresifisme,essentialism, parenialisme and rekonstruksionisme. Departing from the abovephenomenon, this paper tries to unveil the model of Islamic thought in thecontext of the development of education; study of Islamic education schools inIslam which is described in the discussion of which four; 1) The basic concept ofthe development of Islamic education, 2) model of Islamic education developmentthinking, 3) school of Islamic education Islamic education relevance to thepresent, and 4) determining the formulation of Islamic education system Keywords: Models, Islamic Thought, Education Development, Education Schools.